Electrochemical sensor based on multi-walled carbon nanotubes and two-dimensional zeolitic imidazolate framework nanosheets: Application in determining dacarbazine - Somayeh Tajik; Hadi Beitollahi; Fariba Garkani Nejad; Zahra Dourandish; Samuel Adeloju (ADMET and DMPK)
Background and Purpose: Cancer is a serious public health concern, hence the determination of dacarbazine as a significant chemotherapeutic agent is very important. Experimental Approach: In the present work, we describe using a facile method to synthesize a nanocomposite of multi-walled carbon nanotubes (MWCNTs) and two-dimensional zeolitic imidazolate framework nanosheets (2D ZIF-L NSs). The resulting MWCNTs/2D ZIF-L NSs nanocomposite was characterized by field-emission scanning electron microscopy. The MWCNTs/2D ZIF-L NSs nanocomposite was subsequently used to modify a screen-printed carbon electrode (SPCE) to achieve an electrochemical sensing platform for the detection of dacarbazine.